Das Restglied asymptotischer Entwicklung der Dichtefunktionen - Survila, P. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Сурвила. Остаточный член асимптотического разложения для плотностей P. Survila. Tankio funkcijos asimptotinio išdėstymo liekamasis narys